Pengaruh variasi suhu hidrotermal dan aktivator kalium hidroksida (KOH) terhadap kemampuan hydrochar sebagai adsorben pada proses adsorpsi limbah cair metilen biru - Aziz Askaputra; Ahmad T. Yuliansyah (Jurnal Rekayasa Proses, 2020)
Oil palm shell is one of biomass-wastes which is abundantly found in palm oil industries. Its economical value can be enhanced by converting it into hydrochar using a hydrothermal carbonization process (HTC). In this study, preparation of oil palm shell hydrochar was performed and the material was used as adsorbent to remove methylene blue from waste water. Effects of HTC temperature, KOH activator concentration, and adsorption time were studied. Functional groups of hydrochar were evaluated by Fourier transform infrared (FTIR) spectroscopy. Meanwhile, the uptake capacity of hydrochar to adsorp methylene blue was measured by using UV-Vis spectrophotometer. The results showed that dehydration and decarboxylation reactions took place more progressively at the higher temperature of HTC. It was also found that activation process resulted higher removal efficiency of methylene blue. The highest adsorption capacity (16.58 mg/g, with removal efficiency 99.51%) was obtained by hydrochar prepared by HTC 270°C, KOH 1.5 N, and carried out for 80 minutes.